PRINCIPALS’ STRATEGIES FOR THE IMPROVEMENT OF STAFF PERSONNEL ADMINISTRATION OF SECONDARY SCHOOLS IN ENUGU NORTH EDUCATION ZONE, ENUGU STATE, NIGERIA - Gladys, O.; Ugwu, Ifeanyichukwu; Oparaji, Israel Chijiuka (International Journal of Research -GRANTHAALAYAH, 2020)
This study investigated the principals’ strategies for the improvement of staff personnel administration of secondary schools in Enugu North Education Zone, Enugu state. The study has two purposes, and was guided by 2 research questions and two hypothesis. It adopted a descriptive research design. The population of the study consist 108 secondary school principals and 1,423 secondary school teachers in Enugu North Education Zone, Enugu state. Through multistage and simple random sampling, the sample size of 16 secondary school principals and 170 secondary school teachers were drawn. The instrument for data collection was a 20-item structured questionnaire. The questionnaire has two sections: section A for secondary school principals while section B is for secondary school teachers. The instrument were validated by three experts: two from Educational Management and Policy while the other one from Department of Measurement and Evaluation, all from faculty of education, Nnamdi Azikiwe University, after which they were subjected to test-retest on 15 secondary school principal and 15 secondary school teachers in Enugu West Education zone. Their scores were computed with Cronbach Alpha technique which yielded a reliability value of 0.75 which indicates that the instruments were valid. Data collected in this study were analyzed using arithmetic mean and standard deviation while the hypotheses were tested at 0.05 level of significance. Findings reveal that strategies adopted by secondary school principals in for the improvement of staff personnel administration include: involving teachers in decision making, teacher motivation, good leadership, assigning teachers with official responsibilities among others. It was also revealed that teachers were enhanced with s good leadership strategies from principals, motivation and engaging staff in re-training exercise.